2018
DOI: 10.1017/s2040174418000387
|View full text |Cite
|
Sign up to set email alerts
|

At the heart of programming: the role of micro-RNAs

Abstract: Epidemiological and experimental observations tend to prove that environment, lifestyle or nutritional challenges influence heart functions together with genetic factors. Furthermore, when occurring during sensitive windows of heart development, these environmental challenges can induce an 'altered programming' of heart development and shape the future heart disease risk. In the etiology of heart diseases driven by environmental challenges, epigenetics has been highlighted as an underlying mechanism, constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 345 publications
(237 reference statements)
0
5
0
1
Order By: Relevance
“…In the early origins of heart diseases, epigenetic mechanisms are likely key players. In particular, micro-RNAs, which belong to small non-coding RNAs (around 22 nucleotides in length) involved in each step of heart development, seem to play a crucial role in the unfavorable programming of heart diseases 8 . By controlling about 60% of all protein-coding genes in mammals, micro-RNAs are considered as significant post-transcriptional regulators of gene expression 9 , and regulate almost all biological processes including development, differentiation, proliferation, apoptosis, metabolism and tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…In the early origins of heart diseases, epigenetic mechanisms are likely key players. In particular, micro-RNAs, which belong to small non-coding RNAs (around 22 nucleotides in length) involved in each step of heart development, seem to play a crucial role in the unfavorable programming of heart diseases 8 . By controlling about 60% of all protein-coding genes in mammals, micro-RNAs are considered as significant post-transcriptional regulators of gene expression 9 , and regulate almost all biological processes including development, differentiation, proliferation, apoptosis, metabolism and tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms that should be further explored are the epigenetic regulations of SERCA2 expression. Indeed, in the developmental origins of health and disease, epigenetics is described as a key player [ 29 ]. Interestingly, studies reported DNA methylation [ 30 ] and microRNAs [ 31 , 32 ] as regulators of SERCA2.…”
Section: Discussionmentioning
confidence: 99%
“…These exposures alter one's cardiac metabolism and the microRNAs involved in each development stage of the heart and seem to play a crucial role in the unfavorable programming of CVDs. 22 Thus, diets that are restrictive in macronutrients and/or obesogenic diets, characterized by the excess of calories, sugars, and lipids, can lead to malnutrition and, if consumed by the mother during gestation and/ or lactation, can be equally capable of programming the offspring for cardiometabolic diseases. 23 Maternal malnutrition (F0 generation) programs its direct descendants (F1 generation), and it is capable of programming its subsequent generations (F2, F3, for example).…”
Section: Maternal Malnutrition: Lack or Excess Of Macronutrientsmentioning
confidence: 99%